Bridge Structure Dynamic Analysis under Vessel Impact Loading considering Soil-Pile Interaction and Linear Soil Stiffness Approximation. (17th March 2019) - Zhang, Jingfeng; Li, Xiaozhen; Jing, Yuan; Han, Wanshui
Abstract : The appropriate modeling of the soil-pile interaction (SPI) is critical to get the reasonable dynamic responses of bridge structure under impact loading. Of various SPI modeling approaches, utilizing p-y and t-z curves is a common method to represent the nonlinear lateral resistance and skin friction of pile-surrounding soil. This paper accomplished SPI modeling for the bridge pylon impact analysis with compression-only nonlinear springs and linear dashpots. The kinematic interaction and pile group effect were incorporated into the SPI. A variety of pylon impact analyses were conducted under energy-variation impact loads. The structure dynamic responses were compared and discussed considering the influences of pile group effect, soil damping, and axial t-z spring. An approximate approach was proposed to derive the linearized stiffness of soil for the purpose of engineering calculation. It was concluded from the extensive simulations that the impact load generated from higher initial energy induced more significant structural responses and larger soil inelastic deformation than smaller initial energy. The piles in the leading row possessed larger bending moments, whereas they exhibited smaller pile deformation than the responses of trailing row piles. Soil damping applied in SPI played positive roles on the reduction of structural responses. Replacing the t-z spring by fixing the degree-of-freedom (DOF) in the vertical direction was capable to yield satisfactory results of structural responses. The proposed linear soil stiffness was demonstrated to be applicable in the SPI modeling of structure impact analysis.